The Impact of Knowledge Management on Institutional Performance: An Applied Study on Greater Amman Municipality - Al-Jaafreh, Amer Zaal (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the impact of knowledge management on institutional performance from the viewpoint of the employees of the Greater Amman Municipality. To achieve the objectives of the study, a questionnaire was built for the purpose of data collection. The study sample consisted of 89 employees from the Greater Amman Municipality- Main Center-, from the executive administrative level, they were selected using a simple random sample method, and a set of appropriate statistical methods were used to analyze the study data. Results of study were found, the most important of which was that the availability of knowledge management in the Greater Amman Municipality from the point of view of the Secretariat staff came to a high degree, also, the level of institutional performance in the Greater Amman Municipality has come to a high degree, and there is an effect between knowledge management and institutional performance. The study recommends the necessity of continuing to provide the necessary knowledge management requirements for workers in the Greater Amman Municipality, in order to improve the performance of its employees, and thus achieve its objectives continuously.